PENGGUNAAN AKTIVITAS KIMIA BERBASIS SENI UNTUK MENINGKATKAN PEMAHAMAN KONSEP KIMIA SISWA DI SMA NEGERI 2 PADANG BOLAK - Siti Aminah; Abubakar Abubakar; Fatma Suryani Harahap (Universitas Muhammadiyah Tapanuli Selatan, 2019)
This study aims to improve student chemistry learning activities and to understand students' chemical concepts through the use of art-based chemistry activities. This research is a classroom action research conducted in 2 cycles, with each cycle consisting of planning, implementation, observation, and reflection. The subjects of this study were students of class X MIA Padang Bolak State High School 2, which numbered 30 students. Data sources come from teachers and students. Data collection techniques through observation, tests, questionnaires, and interviews, then analysed using qualitative descriptive. The results showed an increase in the understanding of students' chemical concepts in the first cycle obtained 53.33% and the second cycle 83.33%. The percentage of biochemical activity of students in the first cycle was 58.68% and the second cycle was 81.06%. Based on the results of the study, it can conclude that the use of art-based chemical activities could improve students 'understanding of chemical concepts and students' chemical learning activities in synthetic bonding material in class X MIA, SMA Negeri 2 Padang Bolak 2018/2019 academic year. Keywords: Classroom Action Research, Art-based Chemistry Activities, Understanding Concept.